Biosíntesis de alcaloides bencilisoquinolínicos - Christian Anabí Riley-Saldaña; Alma Rosa González-Esquinca; Iván De-La-Cruz Chacón (Universitas Scientiarum)
Benzylisoquinoline alkaloid biosynthesis. The benzylisoquinoline alkaloids (BIA) are specialized metabolites with an ancient phylogeneticdistribution, but still preserved in modern clades. Some of them, such as morphine, sanguinerine or berberine, are important for modernmedicine. This review discusses the highlights of the current state of the biosynthesis of BIA. There have been studies that show thebiosynthesis of 22 of these nitrogenous metabolites. In their formation there are 43 enzymes grouped into oxidoreductases, transferasesand lyases, which in some cases represent atypical examples of the manner in which the secondary metabolism diversification wasoriginated. Two of these examples are the cytochrome proteins P450 (P450), with catalytic activities for ABI route, or the norcoclaurinesynthase enzyme (NCS), which share substantial identity with defense allergenic proteins. Likewise, there are genetic advances thathave produced the characterization of 30 enzymes, allowing knowledge of regulatory processes. Another interesting aspect is thecompartmentation of the biosynthesis sites and accumulation of BIA, since in several cases they are spatially separated and in differentspecies, or in the same species several types of cells may be involved. This has suggested intra and intercellular transport of alkaloids,precursors and enzymes, and it has been documented berberine transport between the cytoplasm and the vacuoles of storage. The picturefor the biosynthesis of BIA has been constructed with exemplary studies of alkaloids with pharmacological importance.